Bacteria Contaminants in Meatballs Sold in the Market Padang City Raya - Sutra, Bunga; Gustina Indriati; Megahati S, Ruth Rize Paas (RADINKA JAYA UTAMA PUBLISHER, 2024)
Meatballs are a processed meat product that has high nutrition. The maximum shelf life for meatballs made from meat is 1 day (12 hours). Storing meat foods at inappropriate temperatures, such as room temperature, greatly facilitates the growth of microbes. The marketplace for meatballs in traditional markets in the city of Padang is still sold on the streets at open-air temperatures without using sufficient refrigeration. The possibility of contamination with microorganisms is very large. This research aims to determine the suitability and quality of meatballs sold at Pasar Raya Padang City by examining the Total Plate Count (TPC) and identifying the types of bacteria that contaminate meatballs sold at Pasar Raya Padang City. The research results showed that the amount of microbial contamination in meatballs varied, namely 1.9x10 6, 7.5x10 6, 5.6x10 6, 1.8x10 6, 8.6x10 6, and 9.2x10 6. The results of this study showed that the meatball samples had microbial contamination greater than 10 5 CFU/gr or did not meet SNI standards. Based on macroscopic and microscopic morphological identification as well as biochemical reactions, all isolates were classified as bacteria from the genus Bacillus